VD_FINDINFO HC / 2016 / 77 vom 2. Dezember 2015 - VD Tribunal cantonal (2015)
FRAIS JUDICIAIRES, DÉPENS, DÉCISION DE RENVOI, TRIBUNAL FÉDÉRAL | 67 LTF, 68 al. 5 LTF, 106 al. 1 CPC (CH), 106 al. 2 CPC (CH), 95 CPC (CH)